BIOPHYSICAL MECHANISMS OF TRANSCRANIAL MAGNETIC STIMULATION IN MIGRAINE (International journal of artificial intelligence, 2026)
This research work presents an analysis of the biophysical mechanisms underlying the therapeutic effects of the Transcranial Magnetic Stimulation in patients with chronic migraine. The study focuses on the influence of TMS on cortical excitability, neuronal membrane polarization and modulation of synaptic transmission.